Info and Index of the EDUCARE Journal, Issue of February 2016 - Journal, Editor EDUCARE (EDUCARE, 2016)
EDUCARE journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the educational studies in general and its various aspects. Analysis will be practical and rigorous in nature. The EDUCARE journal, with Print ISSN 1979-7877, was firstly published on August 17, 2008, in the context to commemorate the Independence Day in Indonesia. Since issue of February 2009 to date, the EDUCARE journal has been organized by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE journal is published twice a year, i.e. every August and February.Bandung, Indonesia: February 28, 2016.Andi SUWIRTA, M.Hum.Chairperson of ASPENSI in Bandung, West Java, Indonesia.Â